2011
DOI: 10.1016/j.bbabio.2010.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic management of brain cancer

Abstract: Malignant brain tumors are a significant health problem in children and adults. Conventional therapeutic approaches have been largely unsuccessful in providing long-term management. As primarily a metabolic disease, malignant brain cancer can be managed through changes in metabolic environment. In contrast to normal neurons and glia, which readily transition to ketone bodies (β-hydroxybutyrate) for energy under reduced glucose, malignant brain tumors are strongly dependent on glycolysis for energy. The transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
124
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(128 citation statements)
references
References 235 publications
3
124
0
1
Order By: Relevance
“…The combination of CR and the KD [calorie restricted KD (RKD)] has also been studied as a cancer therapy. The anti-proliferative and anti-angiogenic effects of CR and the RKD have been substantiated in a number of studies using experimental mouse and human brain tumor models ( 13,31,(47)(48)(49)(50). Angiogenesis is currently a therapeutic target for the treatment of gliomas, and bevacizumab, a monoclonal antibody targeting the proangiogenic factor VEGF, is the only US Food and Drug Administration-approved molecular drug for use in GBMs.…”
Section: The Kd and Caloric Restriction In Preclinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of CR and the KD [calorie restricted KD (RKD)] has also been studied as a cancer therapy. The anti-proliferative and anti-angiogenic effects of CR and the RKD have been substantiated in a number of studies using experimental mouse and human brain tumor models ( 13,31,(47)(48)(49)(50). Angiogenesis is currently a therapeutic target for the treatment of gliomas, and bevacizumab, a monoclonal antibody targeting the proangiogenic factor VEGF, is the only US Food and Drug Administration-approved molecular drug for use in GBMs.…”
Section: The Kd and Caloric Restriction In Preclinical Studiesmentioning
confidence: 99%
“…Unlike normal brain cells, many tumor cells cannot utilize ketones effectively due to their various genetic and mitochondrial defects, and must rely on glucose as their primary energy source ( 13,(30)(31)(32)(33)(34)(35). Ketone bodies may also be toxic to some human tumor cells (36)(37)(38).…”
Section: Tumor Metabolismmentioning
confidence: 99%
“…For example, cancer cells differ from normal cells in having high metabolic needs for the purpose of proliferation, using aerobic glycolysisthe Warburg effect-whereby glucose is metabolized into lactate for energy, regardless of oxygen availability. This concept has been previously invoked to link a beneficial effect of the ketogenic diet or calorie restriction to slow the growth of brain tumors (30). Given the great diversity of cell types and functions in the CNS and their varying energy requirements, this idea has fundamental implications as to how we attempt to unravel the energetic principles by which dietary therapies work.…”
Section: Basic Science Advancesmentioning
confidence: 99%
“…It has been found that there is a balance in cancer cell's growth between the availability of energy, sufficient macromolecular synthesis for increased growth, modulation of reactive oxygen species (ROS), nutritional needs of cancer cells, metabolomics, and proteomics of tumors. [13] A lot of studies have been done to fight with cancer cells on the basis of Warburg effect. Reducing the amount of glucose and providing lactate have been tried to challenge the cancer metabolism however new techniques such as the discoveries of oncogenes, tumor suppressor genes, growth factor pathways, molecular subtypes of cancers have overshadowed the Warburg effect recently.…”
Section: Metabolism Of Tumor Cellsmentioning
confidence: 99%